ELECTRONIC PUBLIC INVOLVEMENT: MODERN CHALLENGES FOR KAZAKHSTAN - Panzabekova A.Zh.; Zhanbozova A.B.; Zhumanazarov K.B. (Academic Journal of Physical and Chemical Sciences, 2020)
The article discusses the impact of Internet technologies on daily life of Kazakhstan population, determines the level of the population involvement in electronic processes. Noting the positive impact of electronic involvement of the population on the quality of life, the author focuses on the challenges formed as a result of the comprehensive penetration of Internet technologies in various socio-economic spheres that require state intervention. In characterizing these challenges the author suggests response to action by the state. At the same time, citing high speed and strong impact of changes in Internet technology sphere, the author notes the difficulty of responding to these challenges in an appropriate way. The research hypothesis is that the nature of the challenges associated with the development and impact of Internet technologies on the life of society is changing at a faster pace than the state can respond to these changes, and this trend will continue in the future. In this regard, the author proposes to take measures to reform the system of vocational education with a bias on adaptability of competences and skills of students by strengthening the practical part of education. The author also proposes to change the nature of the organization of scientific activities by combining the efforts of business, science and the state in solving important problems for society, which will allow to share the risks associated with the development of new technologies and innovative solutions.